Where the global meets the local : South African youth and their experience of global media - Strelitz, Larry Nathan (Rhodes University, Faculty of Humanities, Department of Sociology, 2003)
Within the context of debates concerning the impact of global media on local youth, this study explores how a sample of South African youth responds to texts which were produced internationally, but distributed locally. Recognising the profound rootedness of media consumption in everyday life, the research examines the way these youth, differentially embedded in the South African economic and ideological formation, use these texts as part of their ongoing attempts to make sense of their lives. The study rejects the 'either/or' formulations that often accompany competing structuralist and culturalist approaches to text/audience relationships. Instead, using a combination of quantitative and qualitative research methods, it seeks to highlight the interplay between agency and structure, between individual choice and the structuring of experience by wider social and historical factors. The findings of the study point to the complex individual and social reasons that lie behind media consumption choices, and the diverse (and socially patterned) reasons why local audiences are either attracted to, or reject, global media. These and other findings, the study argues, highlight the deficiencies of the media imperialism thesis with its definitive claims for cultural homogenisation, seen as the primary, or most politically significant, effect of the globalisation of media. As such, this study should be read as a dialogue with those schools of thought that take a more unequivocal point of view on the impact of globalised media culture.
Keywords: Mass media and youth -- South Africa; Mass media -- Sociological aspects; Mass media and culture -- South Africa; Youth -- South Africa